(untitled) (Linguostylistic Studies, 2020)
The article highlights the role of Lesya Ukrainka’s idiolect in the history of the Ukrainian literary language. The writer enriched her artistic, scientific and journalistic styles, supplemented her epistolary and translated literature. Lesia Ukrainka’s idiolect significantly expanded the expressive possibilities of literary language, took it beyond Ukrainian realities, and brought the Ukrainian reader closer to classical and European literature: translations of works by Homer, Dante, Byron, Shakespeare, and others. The linguistic aesthetics of Lesya Ukrainka’s poetry was formed on the basis of vernacular and folk poetic language in combination with the literary and written traditions of the Ukrainian classics. The vocabulary of Lesya Ukrainka’s poems demonstrates a high level of the Ukrainian literary language development. Lesya Ukrainka’s poetry conveys complex concepts of art, aesthetics, science, including philosophy, psychology, history, art, and aesthetics. We can find verbal incarnations of the image of the Word in the idiolect of the writer. Most of the events in Lesya Ukrainka’s plays take place in Ancient Greece, Ancient Rome, Spain, Egypt, Germany, North America and other countries. Lesya Ukrainka’s dramas are rich in aphorisms - individual-author maxims. Most of the aphorisms concern the artistic theme of slavery, slavery - freedom, liberty. Various socio-political topics are among the civic interests of the writer, which are reflected in her journalistic works. Lesya Ukrainka is the author of literary-critical and scientific works. The idiolect of the writer significantly complements her epistolary legacy. She adhered to Eastern Ukrainian language traditions and consistently used lexical and grammatical language forms of Western Ukraine.